Detection of low numbers of microplastics in North Sea fish using strict quality assurance criteria. Issue 1 (15th September 2017) - Hermsen, Enya; Pompe, Renske; Besseling, Ellen; Koelmans, Albert A.
Abstract: We investigated 400 individual fish of four North Sea species: Atlantic Herring, Sprat, Common Dab, and Whiting on ingestion of > 20 μm microplastic. Strict quality assurance criteria were followed in order to control contamination during the study. Two plastic particles were found in only 1 (a Sprat) out of 400 individuals (0.25%, with a 95% confidence interval of 0.09–1.1%). The particles were identified to consist of polymethylmethacrylate (PMMA) through FTIR spectroscopy. No contamination occurred during the study, showing the method applied to be suitable for microplastic ingestion studies in biota. We discuss the low particle count for North Sea fish with those in other studies and suggest a relation between reported particle count and degree of quality assurance applied. Microplastic ingestion by fish may be less common than thought initially, with low incidence shown in this study, and other studies adhering to strict quality assurance criteria. Graphical abstract: Highlights: We investigated 400 fish individuals of four North Sea species. Strict quality assurance criteria were followed in order to control contamination. Two plastic particles were found in only one fish individual: a Sprat. FTIR analysis identified the particles as polymethylmethacrylate microbeads. We suggest a link between reported particle count and quality control in studies.